Effects of elevated carbon dioxide on arbuscular mycorrhizal fungi activities and soil microbial properties in soybean (Glycine max L. Merrill) rhizosphere - Nurudeen Olatunbosun Adeyemi; Muftau Olaoye Atayese; Michael Dare; Adebanke Olubode (Acta Fytotechnica et Zootechnica, 2020)
Arbuscular mycorrhizal fungi (AMF) help in promoting plant growth and mediating key belowground processes, however, AMF responses to the continuous increase in the atmospheric carbon dioxide (CO2 ) is yet elusive. This has led to considerable interest in the impacts elevated CO2 on AMF and belowground processes in recent years. The present study investigated the effect of elevated CO2 on AMF sporulation and root colonization and soil microbial properties in the rhizosphere of soybean. The pot experiment consisted of two levels of CO2 (ambient; 350 ppm and elevated; 550 ppm) and three soybean cultivars (TGx 1440-1E, TGx 1448-2F and TGx 1480-2F) conducted in open top chambers, laid out in randomized complete block design, replicated thrice. The results showed that elevated CO2 increased the AMF spore density and root colonization of the soybean cultivars. Elevated CO2 increased the microbial biomass carbon (34.2–45.4%), microbial biomass nitrogen (44.6–54.9%), soil nitrogen (30.3–50.6%), available phosphorus (20.8–45.7%) in the rhizosphere of the soybean cultivars compared to the ambient CO2 . These could have resulted in increased plant biomass, pod number, 100-seed weight and seed yield under elevated CO2 . From the results of this study, increased atmospheric CO2 regulates AMF activities, microbial properties and improve soybean performance. Thus, this study may help to a better understanding of the responses of AMF and belowground process with increasing atmospheric CO2.